Integrated Synthesis of Thienyl Thioethers and Thieno[3,2-b]thiophenes via 1-Benzothiophen-3(2H)-ones - Mitsudo, Koichi; Habara, Nanae; Kobashi, Yoshiaki; Kurimoto, Yuji; Mandai, Hiroki; Suga, Seiji (Synlett, 2020)
A one-pot procedure for the synthesis of thienyl thioethers is described. Several thienyl thioethers were synthesized by a TfOH-promoted Friedel–Crafts-type cyclization, a subsequent nucleophilic attack by an arenethiol, and dehydration. This protocol was successfully applied to the synthesis of thienoacene derivatives by using a Pd-catalyzed dehydrogenative cyclization.
Keywords: thienyl thioethers; thioetherification; one-pot synthesis; metal-free; halide-free; thienoacenes